Notes on Chisosa (Araneae, Pholcidae), with the description of a new species from Mexico - Huber, Bernhard A.; Meng, Guanliang; Valdez-Mondragón, Alejandro (Zootaxa, 2024)
The genus Chisosa Huber, 2000 previously included only three species of small to tiny North American and Caribbean spiders that are rare in collections and poorly studied. Originally placed in the subfamily Ninetinae, Chisosa is currently considered a representative of Arteminae, close to the North American genus Physocyclus Simon, 1893. This placement has been suggested by molecular data, and it affects the interpretation of morphological characters that were originally thought to support the monophyly of Chisosa: they are shared with Physocyclus and thus plesiomorphic for Chisosa. Here we describe a new species from Mexico, C. calapa sp. nov., and restudy in detail the morphology (incl. ultrastructure) of the type species C. diluta (Gertsch & Mulaik, 1940) and of C. caquetio Huber, 2019, based on newly collected material. We document further similarities with Physocyclus but find only weak morphological support for the monophyly of Chisosa (body size reduction and short legs). In addition, we document surprisingly large genetic distances among C. caquetio specimens from Curaçao (>14% CO1 K2P distances), possibly indicating species limits. Finally, we propose that the Dominican amber genus Serratochorus Wunderlich, 1988, based on a single male specimen, is also phylogenetically close to Chisosa and should be included in future studies on these enigmatic spiders.